FENOMENA MARRIAGE IS SCARY: TANTANGAN KONTEMPORER TERHADAP IMPLEMENTASI UU PERKAWINAN DI INDONESIA - Imam Faishol (Al-Usroh : Jurnal Hukum Keluarga Islam, 2025)
The widespread phenomenon of “Marriage is Scary” on social media represents a shift in the perception of Indonesian Generation Z towards the institution of marriage. This study aims to analyze the implications of this phenomenon on the implementation of Law Number 1 of 1974 concerning Marriage. Through a socio-legal approach, the study reveals that the fear of marriage triggered by economic, psychological, and socio-cultural factors has created structural challenges for marriage law, which is built on normative assumptions about marriage as a desirable social norm. Data from the Central Statistics Agency shows a significant and sustained decline in the number of marriages from 2,110,776 (2014) to around 1,478,302 (2024), confirming the real impact of this phenomenon and signaling a change in social paradigm. The research findings reveal three main challenges: (1) the irrelevance of the Ministry of Religious Affairs' marriage guidance function, (2) disruption to the marriage registration system and population projections, and (3) regulatory gaps that do not accommodate the phenomenon of delayed and reluctant marriage. The study concludes that the Marriage Law requires a paradigmatic reorientation that is responsive to social change and recommends a holistic, integrative approach that encompasses legal, economic, and psychological aspects.